2022
DOI: 10.7883/yoken.jjid.2021.076
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Analysis of Gallbladder Wall Thickness as a Marker for Bleeding Risk and Need for Transfusion in Dengue Patients

Abstract: Predictive analysis on gall bladder wall thickness as a marker for bleeding risk and need of transfusion in dengue patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Studies suggested that using GBWT as a noninvasive predictor of gastroesophageal varices in cirrhotic and portal hypertension patients [ 18 ]. Other reports investigate GBWT as a marker of bleeding risk in patients with dengue fever [ 19 ]. The surgeon has a 14.6% chance, based on our data, of operating a patient with a GBWT > 5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested that using GBWT as a noninvasive predictor of gastroesophageal varices in cirrhotic and portal hypertension patients [ 18 ]. Other reports investigate GBWT as a marker of bleeding risk in patients with dengue fever [ 19 ]. The surgeon has a 14.6% chance, based on our data, of operating a patient with a GBWT > 5 mm.…”
Section: Discussionmentioning
confidence: 99%